Recurrence and mortality prognostic factors in childhood adrenocortical tumors: Analysis from the Brazilian National Institute of Cancer experience. (18th May 2016) - Bulzico, Daniel; de Faria, Paulo Antônio Silvestre; de Paula, Marcela Pessoa; Bordallo, Maria Alice Neves; Pessoa, Cencita H. C. N.; Corbo, Rossana; Ferman, Sima; Vaisman, Mario; Neto, Leonardo Vieira
ABSTRACT: Prognostic markers that can help identifying precocious risk of unfavorable outcomes in patients with childhood adrenocortical tumors (ACTs) are still unclear. This observational and retrospective study aimed to identify clinical and pathology prognostic factors of recurrence and death in a tertiary cancer center population. Clinical, pathology, demographic, staging, and therapy data from patients with childhood ACT (median age: 3.6 years) treated at the Brazilian National Institute of Cancer between 1997 and 2015 were assessed. Univariate and bivariate analyses were used to study the association of clinical and pathology characteristics with recurrence and mortality. Recurrence and disease-related mortality were the main outcomes. Twenty-seven patients were included. Complete tumor resection was performed in 21 cases. The median tumor size was 8.2 cm. Mitotane was the most common adjuvant/palliative therapy ( n = 13). Recurrence occurred in 6 patients, after a median time of 7.2 months, and was more common among those with larger tumors ( P =.008), higher Weiss score ( P =.001), and microscopic tumoral necrosis ( P =.002). Ten patients died from the disease. Older age ( P =.04), larger tumor size ( P =.002), metastatic disease ( P =.003), previous recurrence ( P =.003), incomplete resection ( P =.002), intraoperative tumor spillage ( P =.005), higher Weiss score ( P =.03), microscopic necrosis ( P =.005), and capsular invasion ( P =.02) were all associated with increased death risk. Even though complete tumor resection was performed in most cases, a considerable number of cases of childhood ACT resulted in recurrence and death. Early identification of unfavorable outcomes is essential to determine ideal therapy and appropriate surveillance.